Social Fitness and Resilience A Review of Relevant Constructs, Measures, and Links to Well-Being - McGene, Juliana (RAND Corporation, 2013)
One of a series of reports designed to support Air Force leadership in promoting resilience among Airmen, its civilian employees, and Air Force family members, this report examines social fitness, or the combination of resources from social connections that influence how individuals respond to stressful circumstances. It assesses the current social fitness constructs and measures in scientific literature to identify methods of increasing social connectedness and support among U.S. Airmen and their families.